2011
DOI: 10.1103/physrevlett.106.125702
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Glass Transition on the Liquid-Gas Spinodal Decomposition

Abstract: We use large-scale molecular dynamics simulations to study the kinetics of the liquid-gas phase separation if the temperature is lowered across the glass transition of the dense phase. We observe a gradual change from phase separated systems at high temperatures to nonequilibrium, gel-like structures that evolve very slowly at low temperatures. The microscopic mechanisms responsible for the coarsening strongly depend on temperature, and change from diffusive motion at high temperature to a strongly intermitten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
156
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(166 citation statements)
references
References 28 publications
9
156
0
1
Order By: Relevance
“…A more recent work on a low density gel reported instead subdiffusive behaviour [37]. At a more coarse-grained level, it was suggested that localised bondbreaking events in gels may result in compressed exponentials [38], a mean-field scenario that was recently revisited using a mesoscopic elasto-plastic model for generic glassy materials [39], in which the gel structure however plays no direct role.Using large-scale numerical simulations of a particlebased model for gel formation [13,14], we show that the spontaneous microscopic aging dynamics during gelation possesses all anomalous signatures reported experimentally. We find a subdiffusive aging dynamics at short lengthscales, corresponding to caged particle motion inside the gel strands, crossing over to superdiffusive relaxation at larger lengthscales triggered by intermittent snapping of the fractal network.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…A more recent work on a low density gel reported instead subdiffusive behaviour [37]. At a more coarse-grained level, it was suggested that localised bondbreaking events in gels may result in compressed exponentials [38], a mean-field scenario that was recently revisited using a mesoscopic elasto-plastic model for generic glassy materials [39], in which the gel structure however plays no direct role.Using large-scale numerical simulations of a particlebased model for gel formation [13,14], we show that the spontaneous microscopic aging dynamics during gelation possesses all anomalous signatures reported experimentally. We find a subdiffusive aging dynamics at short lengthscales, corresponding to caged particle motion inside the gel strands, crossing over to superdiffusive relaxation at larger lengthscales triggered by intermittent snapping of the fractal network.…”
mentioning
confidence: 76%
“…Using large-scale numerical simulations of a particlebased model for gel formation [13,14], we show that the spontaneous microscopic aging dynamics during gelation possesses all anomalous signatures reported experimentally. We find a subdiffusive aging dynamics at short lengthscales, corresponding to caged particle motion inside the gel strands, crossing over to superdiffusive relaxation at larger lengthscales triggered by intermittent snapping of the fractal network.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In recent years a number of approaches for simulating colloidal gelation have been proposed, including shortrange isotropic interactions [21][22][23][24], valence-limited and patchy-particle models [25][26][27], dipolar particles [28], and anisotropic effective interactions [18,29,30]. We follow here this latter approach, using an effective interaction that includes, in the form of a three-body term, the basic ingredients for a minimal model of particle gels.…”
Section: Introductionmentioning
confidence: 99%